Alternative characterization of forest fire regimes: incorporating spatial patterns - Collins, Brandon M.; Stevens, Jens T.; Miller, Jay D.; Stephens, Scott L.; Brown, Peter M.; North, Malcolm P. (Landscape ecology, 2017)
Context The proportion of fire area that experienced stand-replacing fire effects is an important attribute of individual fires and fire regimes in forests, and this metric has been used to group forest types into characteristic fire regimes. However, relying on proportion alone ignores important spatial characteristics of stand-replacing patches, which can have a strong influence on post-fire vegetation dynamics. Objectives We propose a new more ecologically relevant approach for characterizing spatial patterns of stand-replacing patches to account for potential limitation of conifer seed dispersal. Methods We applied a simple modified logistic function to describe the relationship between the proportion of total stand-replacing patch area and an interior buffer distance on stand-replacing patches. Results This approach robustly distinguishes among different spatial configurations of stand-replacing area in both theoretical and actual fires, and does so uniquely from commonly used descriptors of spatial configuration. Conclusions Our function can be calculated for multiple fires over a given area, allowing for meaningful ecological comparisons of stand-replacing effects among different fires and regions.